Microscopic Mechanism of Cement Improving the Strength of Lime-Fly Ash-Stabilized Yellow River Alluvial Silt - Xiaobin Zhang; Zhiduo Zhu (Advances in Civil Engineering)
Silt is a kind of soil with poor engineering performance. Lime-fly ash- (LF-) stabilized silt has the problem of low early strength. In this study, it is aimed to investigate the effect of cement on improving the strength of LF-stabilized silt and reveal the microscopic mechanism. A fixed percentage of LF (18%) plus different percentages of cement (0%, 2%, 4%, and 6%) were mixed with Yellow River alluvial silt (YRAS). Soil samples for tests were artificially made by compaction in the laboratory. Unconfined compressive strength (UCS) tests were performed on soil samples cured for 7 d, 28 d, 60 d, and 90 d. Scanning electron microscope (SEM) tests, energy dispersive X-ray spectroscopy (EDS) tests, and mercury intrusion porosimetry (MIP) tests were performed on soil samples cured for 7 d and 28 d. UCS results showed that the early strength of LF-stabilized YRAS developed significantly after adding cement. UCS also increased with the increase in cement content and curing time. SEM results revealed the differences in microstructure of LF-stabilized YRAS before and after adding cement. Before adding cement, the main microstructure characteristics included small soil particles, large number of pores, and loose particle arrangement. After adding cement, the main microstructure characteristics included large bonded particles, small number of pores, and dense particle arrangement. The EDS results showed that, after curing for 28 d, the elements of gels in stabilized YRAS had changed, mainly including appearance of C and a significant increase of Ca. MIP results showed that the pores with a size of 1 μm∼10 μm accounted for the largest proportion in stabilized YRAS. The product (mainly C-S-H) of cement hydration mainly filled the pores with a size larger than 10 μm at the early stage. Combining strength results and microresults, the micromechanism of cement improving the strength of LF-stabilized YRAS was discussed.